Labview PID speed controller for DC motor - Effizul Syafrin, Abu Bakar (2008)
This project is about developing a PID (proportional-integration-derivation) controller to control the speed of DC motor. The software used to design the controller is LabVIEW 8.5. The methodology is divided into two parts which is software development and hardware implementation. The works in software development are calculation of DC motor transfer function, simulation to determine the parameter value of PID and developing the software controller. Ziegler-Nichols Closed-Loop Method is used to obtain the value for Kp, Ki and Kd. The last part is to interface the controller with the hardware. After finish both parts, this system can be tune by using the PID value to do the analysis on it response.